Pengaruh dimensi kecerdasan emosi terhadap kreativiti pekerja - Mohd Lokman Sapiee,; Nurul Azza Abdullah,; Fatimah Wati Halim,; Arena Che Kasim,; Muhammad Rozaidi Ahmad Romil, (Penerbit Universiti Kebangsaan Malaysia, 2024)
This study investigates the relationship between emotional intelligence dimensions and employee creativity in a Malaysian non-governmental organization. The research examines how self-awareness, self-management, social awareness, and relationship management influence creative thinking among 165 employees. Using SPSS 25.0 for analysis, the study reveals a positive and significant relationship between all emotional intelligence dimensions and employee creativity. The findings highlight the importance of emotional intelligence in fostering innovation and sustainable performance in modern organizations. The research contributes to the understanding of factors driving employee creativity, crucial for organizational success in the 21st century. Implications for practitioners include the potential benefits of investing in emotional intelligence training to enhance creativity and innovation. For researchers, the study opens new avenues for exploring the mechanisms through which emotional intelligence influences creative thinking, emphasizing the need for cross-cultural studies in various organizational contexts. This research provides valuable insights for both academic and professional audiences, offering a foundation for future studies on employee creativity and suggesting the integration of emotional intelligence development in organizational strategies to drive innovation and performance.